ANALISIS STRATEGI DIGITAL MARKETING DALAM MENINGKATKAN PEMASARAN BATU PERMATA (STUDI KASUS: CV. SINAR MAS JAYA PERMATA) - Anak Agung Istri Agung Dwi Arismayanti; Sephy Lavianto; I Gst. Agung Pramesti Dwi Putri (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
A suitable marketing strategy is very important to implement to develop a sustainable business and get a wider target buyer. The application of digital marketing is an effort that companies can make to get closer to consumers through the application of digital technology. The case study from this research is located in CV. Sinar Mas Jaya Permata which sells gemstones. This study aims to analyze strategies that can be implemented to increase the marketing and sales of gemstones through digital marketing. In addition, this research is descriptive qualitative with interviews and observation. This study also applies the STP strategy (Segmentation, Targeting, Positioning), and SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) to find out the results of the strategies that will be implemented by CV. Sinar Mas Jaya Permata. The results of this SWOT analysis can be used by CV. Sinar Mas Jaya Permata as a problem solving material, increasing marketing and sales.